Topsy and Tim Go to Hospital - Adamson;Jean (London Ladybird books Ltd, 2014)
Tim has fallen out of a tree and bumped his head. He's a little nervous about going to hospital, but he soon finds out how nice the Doctors and Nurses are, and there are lots of other children on the ward to play with too. The only problem now is making sure Topsy doesn't feel left out.